Alcohol consumption is a leading risk for morbidity and mortality; public health initiatives needed - Lakhan, Ram (Nepal Journal of Epidemiology, 2013)
I read the article authored by Dasgupta et al “Alcohol Consumption by workers in automobile repair shops of a slum of Kolkata: An assessment with AUDIT instrument” with great interest. This article was published in the Nepal Journal of Epidemiology in volume 3, issue 3, 2013. Alcoholism leads several health, economic and social problems in the lives of people who consume it. It also affects their families and community. Social issues such as violence, suicide, child neglect, work place absent, conflict in relationship, and divorce are some common outcomes of alcohol consumption. DOI: http://dx.doi.org/10.3126/nje.v3i4.9520